Spatial mode analysis of optical beams carrying monstar disclinations. (9th March 2023) - Vicuña-Hernández, Verónica; Cardano, Filippo; Darvehi, Pegah; Marrucci, Lorenzo; Rubano, Andrea; Piccirillo, Bruno
Abstract: Asymmetric polarization disclinations, such as monstars, can be generated in two distinct ways: (a) by an inseparable superposition of three spatial modes bearing optical vortices with circular polarization states; (b) by using a modulated Poincaré beam, consisting of an inseparable superposition of a circularly-polarized fundamental Gaussian beam TEM00 and a second beam exhibiting an azimuthally-modulated vortex with an m -fold rotational symmetry and the opposite circular polarization. Based on the analysis of the spatial modes indirectly involved into the superposition through the latter method, we investigate its capability of spanning as many disclinations as possible, as well as its capability of enabling effective predictions about the generated patterns, such as relevant geometric features, already at the design stage.